ChemInform Abstract: Gold Nanoparticles Supported on a Layered Double Hydroxide as Efficient Catalysts for the One‐Pot Synthesis of Flavones. Issue 11 (February 2016) - Yatabe, Takafumi; Jin, Xiongjie; Yamaguchi, Kazuya; Mizuno, Noritaka
Abstract: Flavones are prepared from methylphenylketones and aryl aldehydes or benzyl alcohols under oxidizing conditions.